تأثير الاعاقة البصرية على الدافعية للإنجاز لدى المتمدرس الكفيف - الأشراف، نجاة (جامعة الوادي university of Eloued, 2019)
الملخص:عنوان الدراسة: الاعاقة البصرية وعلاقتها بالدافعية للإنجاز لدى عينة من تلاميذ مدرسة صغار المكفوفين بالوادي الرباح والمربين هدفت الدراسة إلى الكشف عن دافعية الانجاز لدى المعاقين بصريا والتحقق من الفروقفي دافعية الانجاز التي تعزى إلى متغيرات (الجنس- العمر –المستوى التعليمي). وقد اعتمدت الدراسة الحالية على المنهج الوصفي الاستكشافي التحليلي الذي يتناسب وموضوع الدراسة، واختيرت العينة بطريقة عشوائية بسيطة وبلغتعينةالدراسة (34) معاقمن مدرسة الصغار المكفوفين بالرباح ولاية الوادي. وتمثلت أدوات الدراسة في مقياس الدافعية للإنجاز من إعداد الباحثة، ومن الأساليب الإحصائية نذكر معامل الارتباط بيرسون واختبار ت لحساب الفروق بين أفراد العينة، وقد تم التحقق من الصدق والثبات للأداة وتوصلت الدراسة إلى النتائج التالية: 1. تتسم السمة العامة لدافعية الانجاز لدى المعاقين بصريا بالانخفاض. 2. لا توجد فروق ذات دلالة إحصائية في دافعية الانجازلدى المعاقين بصريا تبعا لمتغير الجنس (ذكور- إناث). 3. لا توجد فروق ذات دلالة إحصائية في دافعية الانجاز لدى المعاقين بصريا تبعاً لمتغيرالعمر. لا توجد فروق ذات دلالة إحصائية في دافعية لدى المعاقين بصريا تبعاً لمتغير المستوى التعليمي. Résumé :فرنسية أو انجلزية Study Title: Visual disability and its relation to motivation for achievement in a sample of students of the school of young blind in Valley Rabah and educators The study aimed at revealing the motivation of achievement of the visually impaired and check the differences in the motivation of achievement attributed to the variables (Gender - Age - Education Level) The methods of study were used in the measure of psychological rigidity. The statistical methods include Pearson correlation coefficient and test to calculate the differences between the sample members. The accuracy and reliability of the study were verified and the study reached the following results: The current study was based on descriptive analytical exploratory approach that is appropriate to the subject of the study. The sample was selected in a simple random way. The sample of the study was (34) The tools of the study in the measure of motivation for achievement of the preparation of the researcher, and statistical methods to mention correlation coefficient Pearson and test to calculate the differences between the sample members, has been verified the credibility and stability of the tool and the study reached the following results: 1. The general characteristic of the visually impaired achievement of the visually impaired is low. 2. There are no statistically significant differences in the achievement motivation of the visually impaired according to the gender variable (male - female). 3. There are no statistically significant differences in the achievement motivation of the visually impaired according to the age variable. 4. There are no statistically significant differences in motivation among the visually impaired according to the educational level variable
دراسة ميدانية على عينة من تلاميذ مدرسة صغار المكفوفين بالرباح
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: الإعاقة البصرية، الدافعية للإنجاز; Déficience visuelle, motivation à la réussite; Visual impairment, achievement motivation